2011
DOI: 10.1098/rspb.2011.1733
|View full text |Cite
|
Sign up to set email alerts
|

Evolving ecological networks and the emergence of biodiversity patterns across temperature gradients

Abstract: In ectothermic organisms, it is hypothesized that metabolic rates mediate influences of temperature on the ecological and evolutionary processes governing biodiversity. However, it is unclear how and to what extent the influence of temperature on metabolism scales up to shape large-scale diversity patterns. In order to clarify the roles of temperature and metabolism, new theory is needed. Here, we establish such theory and model eco-evolutionary dynamics of trophic networks along a broad temperature gradient. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
56
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(59 citation statements)
references
References 48 publications
3
56
0
Order By: Relevance
“…For example, several studies have investigated the drivers of richness patterns between regions (Goldberg et al 2005;Roy and Goldberg 2007;Yoder and Nuismer 2010). Others have studied community assembly along environmental gradients (McPeek 2008;Stegen et al 2009Stegen et al , 2012aStegen et al , 2012b, and Birand et al (2012) examined speciation, extinction, and range sizes. Similar to these studies, we simulate assembly processes such as competition and coevolution of multiple species (see also Nuismer et al 2010) and analyze the emergent biogeographical patterns.…”
Section: The Model Captures the Essentialsmentioning
confidence: 99%
“…For example, several studies have investigated the drivers of richness patterns between regions (Goldberg et al 2005;Roy and Goldberg 2007;Yoder and Nuismer 2010). Others have studied community assembly along environmental gradients (McPeek 2008;Stegen et al 2009Stegen et al , 2012aStegen et al , 2012b, and Birand et al (2012) examined speciation, extinction, and range sizes. Similar to these studies, we simulate assembly processes such as competition and coevolution of multiple species (see also Nuismer et al 2010) and analyze the emergent biogeographical patterns.…”
Section: The Model Captures the Essentialsmentioning
confidence: 99%
“…In addition, ecological network models have shown the importance of adaptive behavior at the component level for organization, stability, and function at the system level [27]. Such models have been used to identify key constraints on the assembly and evolution of persistent complex networks [28][29][30][31]. Similar modeling approaches may prove useful in a PRN context.…”
Section: Ecological and Evolutionary Implications Of Prnsmentioning
confidence: 99%
“…Indeed, whether the thermal sensitivities of biological traits truly reflect an activation energy remains a contentious issue (Clarke 2004;Gillooly et al 2006;del Rio 2008;Hobbs et al 2013;Corkrey et al 2014). Use of the BA model in ecology has also been criticized, because recent empirical studies have revealed a much wider range of E values (Irlich et al 2009; Knies and Kingsolver 2010;Dell et al 2011;Englund et al 2011) than the 0.6 eV (or sometimes 0.65 eV) originally suggested (Gillooly et al 2001) and which has subsequently so often been used in theoretical studies Vasseur and McCann 2005;Wolfshaar et al 2008;Petchey et al 2010;Rall et al 2010;O'Connor et al 2011;Stegen et al 2012). Understanding the sources of the variation in E within and across species is therefore important, especially because such variation is likely to have nontrivial effects on ecological and evolutionary dynamics (Vasseur and McCann 2005;Dell et al 2011Dell et al , 2014.…”
mentioning
confidence: 99%